Normas de interação e de interpretação na atividade narrativa: implicações para o ensino/aprendizagem - Oliveira, Maria do Socorro (Cadernos de Linguagem e Sociedade, 2010)
Based on ethomethodological analysis, this paper examines norms of speaking that guide narrative activities (norms of interaction) and the meaning that children can construct in these speech events, according to narrative experiences in which they have been involved (norms of interpretation). We demonstrate that the way in which these norms are established in the home/school contexts interferes in the schooling process, and the interactive and interpretative conventions can be identified as causes of success or failure in teaching/learning.